Basic Concepts of Modern Thought on Islamic Religious Education According to Fazlur Rahman's Views - Mukarromaini, Musdhalifatul; Maghribi, Hamdan; Maslamah, Maslamah (Transformatif, 2023)
Education is a system to improve the quality of human life. A nation makes various efforts to improve education in order to create future generations who are intellectual without losing their original traditions. So that future generations are able to compete in following developments in the world of education. in the world of education. Education is a cultural process that is always faced with changing times. Changes Education is very relevant to the needs of society, both in terms of concepts, materials or curriculum, processes, functions, and goals of educational institutions. goals of educational institutions. Islamic education is currently faced with the challenges of modern human life, where in general, modern society is a proactive, individual, and competitive society. In the world of education, technological advances are very undeniable, the existence of knowledge and information that is easily accessed by many people should be able to control existing problems but it turns out that on the contrary, it is getting out of control. due to the impact that occurs in modern society, scientists give birth to their thoughts responding to the phenomena that occur in modern society to influence the lives of modern people. Fazlur Rahman is a scientist who poured his thoughts on modern Islam combining general knowledge and religious knowledge. So that Rahman's ideas are expected to be able to produce a strong personal religion and have adequate knowledge. This research aims to examine the basic concepts of modern Islamic education from the view of Fazlur Rahman